2020
DOI: 10.3390/antibiotics9070412
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Drug Development: A New Approach Is Needed for the Field to Survive and Thrive

Abstract: It is often said that the marketplace for new antibiotics is broken. This notion is supported by the observation that many recently-approved antibiotics to treat drug-resistant bacteria have failed commercially in a spectacular fashion. Today, companies with peak market-cap values in excess of USD 500 million to 1 billion prior to product launch regularly sell for pennies on the dollar a few years after market introduction. It is possible, however, that the market is not as broken as we perceive. That is, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 32 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…At the end of the lytic lifecycle, dsDNA phage encodes holin and endolysin proteins to lyse the bacterial cell wall and additional spanning protein in the case of Gram-negative bacteria to break the outer membrane. Exebacase (also called as CF-301) and N-Rephasin SAL200 (tonabacase) are the lysins used for the treatment of bacterial infections [63,64]. In addition, it has been found that bacteria show no resistance to endolysins due to their mechanism of action and their structure [65].…”
Section: Phage-technology As Effective Antimicrobialsmentioning
confidence: 99%
“…At the end of the lytic lifecycle, dsDNA phage encodes holin and endolysin proteins to lyse the bacterial cell wall and additional spanning protein in the case of Gram-negative bacteria to break the outer membrane. Exebacase (also called as CF-301) and N-Rephasin SAL200 (tonabacase) are the lysins used for the treatment of bacterial infections [63,64]. In addition, it has been found that bacteria show no resistance to endolysins due to their mechanism of action and their structure [65].…”
Section: Phage-technology As Effective Antimicrobialsmentioning
confidence: 99%
“…Yet, in the last two decades, the market for antibiotics has been broken due to the high cost of developing new molecules. As the hope of repeating the therapeutic breakthroughs of the 20th century is rapidly fading away, there is an urgent need to develop novel approaches for the control of antibiotic-resistant bacteria [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2014, only nine antibiotics have been approved that target resistant Gram-negative pathogens ( Table 1 ) and 78% of major pharmaceutical companies have scaled back or cut antibiotic research due to developmental challenges ( PEW, 2021 ). Many of these challenges include monetary costs, time, feasibility of clinical trials, regulatory barriers, and low return on investment ( Luepke and Mohr, 2017 ; Bhavnani et al, 2020 ; Safir et al, 2020 ). As resistance has increased and drug development slowed, pharmacokinetic (PK) and pharmacodynamic (PD) studies have become even more important as a means of optimizing and preserving the agents currently available.…”
Section: Introductionmentioning
confidence: 99%